Consumer Involvement in Brand Positioning (A Study on ITC FMCG Products at Organized Retail outlets) - Mrs. V. Sailaja, Dr. Ponduri.S.B, (International Journal of Scientific Research and Management (IJSRM), 2017)
– Andy Spade Consumer is the king in every business success. In the era of global competition, companies and retailers find new ways to position their brands in consumer minds. Companies are developing integrated marketing plans incorporating wide range of marketing elements to create brand position in the dynamic and competitive environment. The current study is about consumer’s involvement in brand positioning and the affect of various associations of the brand image in Fast Moving Consumer Goods (FMCG) categories. To identify the similarities and differences among the consumers' perceptions of brand positioning, four major FMCG categories of Indian Tobacco Company (ITC) are taken into consideration i.e., Staples, Ready to Eat, Confectionaries and Personal Care. These are chosen to examine the relation between consumer involvement and brand positioning with their respective competitors- General Mills, Nestle’, Britannia, HUL and P&G in the market. The primary data is collected through questionnaire and hypothesis is tested between these four different product categories whether consumer involvement has significant impact on brand positioning or not. The results also inferred that as per customers perception, ITC’s Staples and Ready to Eat categories are positioned number one, and Cadbury’s was positioned first in the Confectionaries and HUL positioned first in the Personal Care categories amongst their respective competitors. We found that the differentiation factor for ITC’s success was due many factors like existing brand image, price, quality, availability, product variants and variety, advertising efforts by enrolling celebrities from Sports and Film Industry. It can be concluded that ITC products have very good brand equity compared to other existing players in the industry because of the familiar brand with other segments of products.